COSTLY FALSE BELIEFS: WHAT SELF-DECEPTION AND PRAGMATIC ENCROACHMENT CAN TELL US ABOUT THE RATIONALITY OF BELIEFS - Sarzano, Melanie (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
In this paper, I compare cases of self-deception and cases of pragmatic encroachment and argue that confronting these cases generates a dilemma about rationality. This dilemma turns on the idea that subjects are motivated to avoid costly false beliefs, and that both cases of self-deception and cases of pragmatic encroachment are caused by an interest to avoid forming costly false beliefs. Even though both types of cases can be explained by the same belief-formation mechanism, only self-deceptive beliefs are irrational: the subjects depicted in high-stakes cases typically used in debates on pragmatic encroachment are, on the contrary, rational. If we find ourselves drawn to this dilemma, we are forced either to accept—against most views presented in the literature—that self-deception is rational or to accept that pragmatic encroachment is irrational. Assuming that both conclusions are undesirable, I argue that this dilemma can be solved. In order to solve this dilemma, I suggest and review several hypotheses aimed at explaining the difference in rationality between the two types of cases, the result of which being that the irrationality of self-deceptive beliefs does not entirely depend on their being formed via a motivationally biased process.